The Discipline Analysis of the Doctors on Filling the Medical Record Conforms of the Accreditation Standards 2018 Version at RSUD Tgk. Chik Ditiro Sigli Kab. Pidie Aceh Province - Khairina, Khairina; Hakim, Lukman; Dachi, Rahmad Al Yakin (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
In Hospital’s Minimum Service Standards, completeness of medical record filling is done 1 x 24 hours after completion of service, with the standard completeness of filling 100% medical record. But in RSUD Tgk. Chik Ditiro Sigli of Pidie Regency was still found incomplete filling in the patient's medical record. The purpose of this study was to analyze the influence of physician discipline on the completeness of the contents of the medical record of inpatients in RSUD Tgk. Chik Ditiro Sigli of Pidie Regency. This research is a survey research with explanatory type. This study was conducted on all general practitioners and specialist doctors RSUD Tgk. Chik Ditiro Sigli of Pidie Regency as many as 65 people and 65 records of medical records of patients in the observation of completeness filling by general practitioners and specialists. Data analysis used multiple linear regression, t test and F test. The results showed that the objective and ability variables, justice had no effect and were not significant to the completeness of the contents of the medic record in RSUD Tgk. Chik Ditiro Sigli of Pidie Regency. While exemplary leadership, waskat, assertiveness and humanitarian relations have a positive and significant impact on the completeness of the contents of medical records at RSUD Tgk. Chik Ditiro Sigli of Pidie Regency. While the variables of remuneration, and sanctions have a negative and significant impact on the completeness of the contents of medical records at RSUD Tgk. Chik Ditiro Sigli of PidieRegency. The variable of human relations is the most dominant variable affecting the completeness of the content of medical record at RSUD Tgk. Chik Ditiro Sigli of Pidie Regency. Thus RSUD Tgk. Chik Ditiro Sigli of Pidie Regency should paid more attention to aspects related to the completeness of filling in the patient's medical record so that the patient's medical record service became more optimal.